Atomic-scale Cu in situ confined in ZIF-8 as a chemical-biomolecular bridge for visible-light-activated therapy of Staphylococcus aureus biofilm-associated skin infections - Xuehua Chen; Tai-Cheng Zhou; Hao Wang; Xilun Wang; Zhiguo Zhu; Changle Wen; Xiaoxiao Shi; Hanglin Li; Yang Tang; Jia Wei (Chemical Engineering Journal, 2026)

Polystyrene microplastic exposure induces hepatic damage via immune-modulated autophagy and ferroptosis in Nile tilapia (Oreochromis niloticus) - Feilong Wang; Xiaolong Fan; Xiaomeng Guo; Na Guo; Tian Gao; Changle Zhao; Yuanyuan Li; Haiyan Xu; Fan Bai; Yixin Chen; Deshou Wang; Lina Sun; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Mechanisms of water-inrush mitigation under alternative grouting strategies during shaft sinking: Solidification-enabled stress–seepage–damage coupling - Wenxin Li; Dan Ma; Jiangyu Wu; Xuefeng Gao; Qiang Li; Changle Xu; Chuanjiu Zhang (Bulletin of Engineering Geology and the Environment, 2026)

Overexpression of β-carotene hydroxylase gene (CiBCH) enhances salt stress tolerance in Arabidopsis thaliana - Ying Sun; Ying Song; Shuaitong Zang; Ruiqing Zhang; Hongyao Li; Qiang Li; Liran Yue; Changle Liu; Miao He (Physiology and Molecular Biology of Plants, 2026)

A novel approach for achieving high enrichment of anammox and nitrogen removal rate in municipal wastewater treatment: A pure biofilm process - Xiaoguang Liu; Changle Li; Yang Zhao; Xiyao Li; Qiong Zhang; Liang Zhang; Yongzhen Peng (Water Research, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Time-dependent biphasic dysregulation of autophagy and innate immunity underlies polystyrene microplastics-induced hepatotoxicity in Nile tilapia - Feilong Wang; Xiaomeng Guo; Na Guo; Xiaolong Fan; Haiyan Xu; Yuanyuan Li; Tian Gao; Yixin Chen; Changle Zhao; Lina Sun; Deshou Wang; Xin Xie; et al. (Aquatic Toxicology, 2026)

Effects of Dietary Protein Sources on Vitellogenin of Female Largemouth Bass (Micropterus salmoides) - Yue Tan; Yang Xu; Li Jia; Youqin Kong; Zhili Ding; Changle Qi; Qiyou Xu (Fishes, 2026)
To investigate the effects of three alternative protein sources—Hermetia illucens larvae meal (HIM), Chlorella meal (CM) and stickwater meal (SWM)—on the vitellogenin in female largemouth bass (Micropterus salmoides), these protein sources were used to replace 0% (control group, FM; containing 40% fishmeal), 25% and 50% of the fishmeal in the diet. A total of seven isonitrogenous and isolipidic diets were formulated (FM, 25% HIM, 50% HIM, 25% CM, 50% CM, 25% SWM and 50% SWM). The healthy female fish with an initial body weight of 353.57 ± 28.12 g were fed the experimental diets for eight weeks. The results showed that the viscerosomatic index, gonadosomatic index and oocyte diameter of broodstock in the 50% HIM group were significantly higher than those in the FM group. The 50% HIM group showed the highest rate of stage IV oocytes and the lowest share of stage II oocytes. Hepatic vitellogenin (Vg) mRNA expression was significantly upregulated in the 50% HIM group, whereas ovarian mRNA expression of Vg and vitellogenin receptor (VgR) was significantly upregulated in the 25% SWM and 50% SWM groups. In conclusion, replacing 50% of dietary fishmeal with Hermetia illucens larvae meal can promote ovarian development in largemouth bass broodstock by increasing the gonadosomatic index and the expression of genes involved in vitellogenin synthesis.

Network pharmacology analysis and experimental validation of modified Taohong Siwu decoction against atherosclerosis - Changle Shao; Wanting Meng; Ke Ning; Mengying Huang; Han Li; Hao Cai; Yanwu Xu; Tao Zuo; Hai-dong Guo (In Vitro Cellular & Developmental Biology - Animal, 2026)

High-entropy metal hexacyanoferrate for excellent capacitive deionization - Changle Li; Binbin Tao; Wenjie Wu; Manal S. Ebaid; Eman A. Ayob; Kaidan Zheng; Zeinhom M. El-Bahy; Xingtao Xu; Yusuke Yamauchi; Jiabao Li (Desalination, 2026)

Reverse temporal spectral signal extraction and deep spectral signal decoupling fusion for detection of SCLB infection process - Guohui Liu; Jinyang Chao; Changle Guo; Lulu An; Yang Liu; Hong Sun; Chunqi Zhang; Mingjia Liu; Zheng Cui; Man Zhang; Minzan Li; Wei Yang (Computers and Electronics in Agriculture, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Curcumin alleviates ferroptosis in CCl₄-induced acute liver injury in vitro: involvement of TXNIP/NLRP3 inhibition and SLC7A11/GSH/GPX4 activation - Wei Zhang; Ziqi Liu; Changle Dong; Huimin Yang; Yunchao Zhang; Shuo Li; Yinsheng Qiu; Lingyun Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Nondestructive testing of grain moisture content and bulk density by microwave reflection quadrature mixing - Chenxiao Li; Changle Fan; Zuoqi Wang; Xuemeng Sun; Qian Song; Yanlei Xu (Journal of Stored Products Research, 2026)

Statistical knowledge-guided multi-classification machine learning modeling scheme for landslide susceptibility levels - Feifei Zhang; Changle Li; Yuewei Wang; Yiyue Wang (Engineering Geology, 2026)

Sidestream phosphorus release enables DPAO-anammox synergy in single-sludge A2/O: Nutrient removal and P recovery from low-C/N municipal wastewater - Yang Zhao; Liang Zhang; Changle Li; Xiaoguang Liu; Jiayuan Deng; Hongxun Hou; Yongzhen Peng (Chemical Engineering Journal, 2026)

Hepatic cyp24a1 serves as a biomarker for diagnosing polystyrene microplastic exposure in Nile tilapia (Oreochromis niloticus) - Feilong Wang; Haiyan Xu; Xiaomeng Guo; Xiaolong Fan; Yuanyuan Li; Tiao Gao; Xin Xie; Na Guo; Fan Bai; Yixin Chen; Changle Zhao; Deshou Wang; et al. (Aquatic Toxicology, 2026)

UAV-borne RGB image and LiDAR fusion for reconstruction of 3D simulated hyperspectral data for crop growth parameter estimation - Weijie Tang; Mingjia Liu; Ruomei Zhao; Guohui Liu; Hong Sun; Changle Guo; Yang Liu; Lulu An; Minzan Li (Computers and Electronics in Agriculture, 2025)

Sustainable intensification of A2/O process through dual anammox pathways: A two-step biofilm-based retrofitting strategy - Yang Zhao; Liang Zhang; Changle Li; Xiaoguang Liu; Xiyao Li; Qiong Zhang; Yongzhen Peng (Journal of Environmental Chemical Engineering, 2025)

Improvement on chlorophyll fluorescence parameters detection of potato leaf based on wavelet cluster analysis - Mingjia Liu; Changle Guo; Zhuoyuan Zhao; Xiaoyang Ma; Hong Sun; Wei Yang; Minzan Li (Computers and Electronics in Agriculture, 2025)

Hydrothermal-KOH activated expired TCM waste into porous carbon for All-Solid-State supercapacitors - Changle Li; Yiqian Liu; Yanlei Zhang (Waste Management, 2025)

H2O2-driven reactive oxygen cascade in g-C3N4/Zn-MOF S-scheme heterojunctions for enhanced solar photocatalytic pollutant removal - Changle Li; Tianzhu Yu; Zhaoxiong Yan; Zhihua Xu; Xianfeng Yang; Qin Li (Journal of Environmental Management, 2025)

Geological disaster causes analysis based on knowledge graph link prediction - Xinya Lei; Changle Li; Yuewei Wang; Weijing Song (Natural Hazards, 2025)

Sustainable production of rare earth elements by recycling NdFeB magnets through sulfation chemistry assisted water leaching process - Junjie Shi; Dong Chen; Qixuan Jiang; Min Chen; Yuchao Qiu; Changle Hou; Jingjing Dong; Jianzhong Li (Minerals Engineering, 2025)

NiAl-LDH–coupled vacancy-rich MnO2 for enhanced room-temperature formaldehyde mineralization - Xianfeng Yang; Tianzhu Yu; Zhihua Xu; Zhikun Li; Jiawei Ye; Zhaoxiong Yan; Changle Li (Journal of Environmental Chemical Engineering, 2025)

Codon usage pattern and genetic diversity in chloroplast genomes of Zanthoxylum species (Sapindales: Rutaceae) - Changle Li; Songping Wu; Jiangbo Nie; Ling Zhou; Yonghong Liu; Yulin Liu (Acta Physiologiae Plantarum, 2025)

Modulated electronic structure and enhanced reactive oxygen species promoting complete decomposition of indoor formaldehyde over bifunctional La-doped CeO2 catalyst - Changle Li; Tianzhu Yu; Meng Zhang; Zhaoxiong Yan; Wenhui Li; Jiawei Ye; Zhihua Xu (Chemical Engineering Journal, 2025)

Sulfation roasting for rare earth recovery from NdFeB scrap: Kinetics, thermodynamics, and phase transformation - Junjie Shi; Dong Chen; Min Chen; Yuchao Qiu; Jingjing Dong; Changle Hou; Fan Zhang; Jianzhong Li (Process Safety and Environmental Protection, 2025)

Unraveling the Molecular Mechanism of Lignin Accumulation in Stipule Thorns of Zanthoxylum bungeanum: Insights from Transcriptomic and Targeted Metabolomic Analysis - Weilong Gao; Ling Zhou; Hao Zhong; Yuan Meng; Changle Li; Jianxin Wang; Jia Yao; Yulin Liu (Journal of Plant Growth Regulation, 2024)

W single-atom mediated singlet oxygen formation on carbon nitride for powerful photocatalytic abatement of organic pollutants - Jiaqi Chen; Zhaoxiong Yan; Yingjie Ding; Guosheng Wang; Changle Li; Zhihua Xu (Chemical Engineering Journal, 2024)

Effects of Soybean Isoflavones on the Growth Performance and Lipid Metabolism of the Juvenile Chinese Mitten Crab Eriocheir sinensis - Mengyu Shi; Yisong He; Jiajun Zheng; Yang Xu; Yue Tan; Li Jia; Liqiao Chen; Jinyun Ye; Changle Qi (Fishes, 2024)
In order to study the effects of soybean isoflavones on the growth performance and lipid metabolism of juvenile Chinese mitten crabs, six experimental diets were formulated by gradient supplementation with 0%, 0.004% and 0.008% soybean isoflavones at different dietary lipid levels (10% and 15%). The groups were named as follows: NF-0 group (10% fat and 0% SIFs), NF-0.004 group (10% fat and 0.004% SIFs), NF-0.008 group (10% fat and 0.008% SIFs), HF-0 group (15% fat and 0% SIFs), HF-0.004 group (15% fat and 0.004% SIFs) and HF-0.008 group (15% fat and 0.008% SIFs). All crabs with an initial weight of 0.4 ± 0.03 g were fed for 8 weeks. The results showed that dietary supplementation with 0.004% or 0.008% SIFs significantly increased the weight gain and specific growth rate of crabs. Diets supplemented with 0.004% or 0.008% SIFs significantly reduced the content of non-esterified free fatty acids and triglycerides in the hepatopancreas of crabs at the 10% dietary lipid level. Dietary SIFs significantly decreased the relative mRNA expressions of elongase of very-long-chain fatty acids 6 (elovl6), triglyceride lipase (tgl), sterol regulatory element-binding protein 1 (srebp-1), carnitine palmitoyltransferase-1a (cpt-1a), fatty acid transporter protein 4 (fatp4), carnitine palmitoyltransferase-2 (cpt-2), Δ9 fatty acyl desaturase (Δ9 fad), carnitine palmitoyltransferase-1b (cpt-1b), fatty acid-binding protein 10 (fabp10) and microsomal triglyceride transfer protein (mttp) in the hepatopancreas of crabs. At the 15% dietary lipid level, 0.008% SIFs significantly increased the relative mRNA expressions of fatty acid-binding protein 3 (fabp3), carnitine acetyltransferase (caat), fatp4, fabp10, tgl, cpt-1a, cpt-1b and cpt-2 and significantly down-regulated the relative mRNA expressions of Δ9 fad and srebp-1. In conclusion, SIFs can improve the growth and utilization of a high-fat diet by inhibiting genes related to lipid synthesis and promoting lipid decomposition in juvenile Chinese mitten crabs.

Effects of Dietary Glutamate on the Growth Performance and Antioxidant Capacity of Juvenile Chinese Mitten Crab (Eriocheir sinensis) - Jiajun Zheng; Yisong He; Mengyu Shi; Li Jia; Yang Xu; Yue Tan; Changle Qi; Jinyun Ye (Fishes, 2024)
In order to explore the effects of glutamate on the growth performance, antioxidant capacity and protein metabolism of juvenile Chinese mitten crab, 0%, 1% and 2% glutamate were supplemented to low protein (30%) and normal protein (35%) diets, respectively. There were 5 parallel tanks in each treatment, and the feeding duration was 8 weeks. The results showed that dietary glutamate did not significantly affect the weight gain of Chinese mitten crab. Diets supplemented with 2% glutamate significantly decreased the crude protein of crabs. The T-AOC of crabs fed the 30% protein diets was significantly lower than crabs fed the 35% protein diets. At 30% protein level, the superoxide dismutase (SOD) activity significantly increased with the increase in glutamate content. Dietary glutamate significantly down-regulated the relative expressions of mTOR, PI3K, S6K1 and 4EBP at 35% protein level. In conclusion, dietary glutamate cannot significantly increase the growth of Chinese mitten crab, but it can improve the antioxidant capacity in Chinese mitten crab under low protein conditions.

The cellular expression patterns of gdnfa and gdnfb in the gonads of Nile tilapia and their differential response to retinoic acid - Lei Liu; Jianeng Li; Changle Zhao; Ximei Qu; Xiang Liu; Deshou Wang; Jing Wei (Theriogenology, 2024)

Integrated transcriptomic and metabolomic analysis reveal the molecular and metabolic basis of flavonoids in Chinese sour jujube fruits in different harvest times - Guolong Li; Zhishu Tang; Zhongxing Song; Xinbo Shi; Changle Liu; Qiang Chen; Hongbo Liu (Postharvest Biology and Technology, 2024)

Modeling of arsenic migration and emission characteristics in coal-fired power plants - Yan Zhao; Cheng Zhang; Lun Ma; Shenghui Yu; Changle Yuan; Junchen Li; Peng Tan; Qingyan Fang; Guangqian Luo; Gang Chen (Journal of Hazardous Materials, 2024)

Functional graphitic carbon nitride/hydroxyapatite heterojunction for robust formaldehyde removal at ambient temperature - Zhihua Xu; Changle Li; Nenghuan Wang; Yingjie Ding; Zhaoxiong Yan; Qin Li (Journal of Environmental Chemical Engineering, 2024)

Hybrid deep learning model for accurate classification of solid waste in the society - Huanping Zhang; Hanhua Cao; Yuhuai Zhou; Changle Gu; Danyu Li (Urban Climate, 2023)

Codon usage bias and genetic diversity in chloroplast genomes of Elaeagnus species (Myrtiflorae: Elaeagnaceae) - Changle Li; Ling Zhou; Jiangbo Nie; Songping Wu; Wei Li; Yonghong Liu; Yulin Liu (Physiology and Molecular Biology of Plants, 2023)

BSA‑seq and genetic mapping identified candidate genes for branching habit in peanut - Jiaowen Pan; Ximeng Zhou; Naveed Ahmad; Kun Zhang; Ronghua Tang; Huiling Zhao; Jing Jiang; Mengdi Tian; Changsheng Li; Aiqin Li; Xianying Zhang; Liangqiong He; et al. (Theoretical and Applied Genetics, 2022)

Insight into the genesis of the Zhaosu Carboniferous Mn carbonate deposit (NW China): constraints from petrography, geochemistry, and C–Mo isotopes - ZhiGuo Dong; ZiDong Peng; ChangLe Wang; BangLu Zhang; LianChang Zhang; Jie Li; Xin Zhang; WenJun Li; Le Zhang (Mineralium Deposita, 2022)

BSA‑seq and genetic mapping reveals AhRt2 as a candidate gene responsible for red testa of peanut - Kun Zhang; Mei Yuan; Han Xia; Liangqiong He; Jing Ma; Mingxiao Wang; Huiling Zhao; Lei Hou; Shuzhen Zhao; Pengcheng Li; Ruizheng Tian; Jiaowen Pan; et al. (Theoretical and Applied Genetics, 2022)

Exogenous application of acetic acid improves the survival rate of cotton by increasing abscisic acid and jasmonic acid contents under drought stress - Chenyang Li; Xiangqiang Kong; Zhen Luo; Weijiang Li; Wei Tang; Dongmei Zhang; Changle Ma; Hezhong Dong (Acta Physiologiae Plantarum, 2021)

Purinergic P2X7 receptor functional genetic polymorphisms are associated with the susceptibility to osteoporosis in Chinese postmenopausal women - Hong Xu; Chengxin Gong; Luling He; Shenqiang Rao; Xingzi Liu; Yijun Nie; Changle Liu; Tao Li; Lu Ding; Yunming Tu; Yuping Yang; Fangfang Hu; et al. (Purinergic Signalling, 2017)

LncRNA NONRATT021972 siRNA attenuates P2X7 receptor expression and inflammatory cytokine production induced by combined high glucose and free fatty acids in PC12 cells - Hong Xu; Luling He; Changle Liu; Lan Tang; Yonghu Xu; Mengqi Xiong; Mei Yang; Yongfang Fan; Fangfang Hu; Xingzi Liu; Lu Ding; Yun Gao; et al. (Purinergic Signalling, 2016)

A novel single-trial event-related potential estimation method based on compressed sensing - Zhihua Huang; Minghong Li; Shangchuan Yang; Yuanye Ma; Changle Zhou (Neuroscience Bulletin, 2013)

Association of CDKN1B gene polymorphisms with susceptibility to breast cancer: a meta-analysis - Heping Xiang; He Li; Weiwei Ge; Weidong Wu; Ming Gao; Wei Wang; Lei Hong; Datong Jiang; Changle Zhang (Molecular Biology Reports, 2013)

A classification-based method to estimate event-related potentials from single trial EEG - ZhiHua Huang; MingHong Li; ChangLe Zhou; YuanYe Ma (Science China Life Sciences, 2012)